(3CYjGf GdYUQ hCYhGf GdfUQs - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj , UdGM GdOjf,J (B764 (3g` s ((3CMeO Hf eSYhO GdfGHdSi s)
(3ChdgG (B:s
(3Ydi Hf YHO GdcQje Hf WQNGf Hf Jbi GdTjN GdGeGe GdYGde YdGA GdOjf CHh GdMSf GHf egPH GdOjf GdMehi GdUaOi s
(3BNQgG (B:s
(3Yjf HUjd GHQGgje Hf Ydi Yjf Yjf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B122s
(3jfJgi HCdbGH MQa GdYjf eY GdJGAs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B315 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B114 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B352s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B24 s
Keywords: (3GdJGQjNs